Depression Promotes Gastroesophageal Reflux Disease: New Evidence Based on Mendelian Randomization - Chen, Gui; Xie, Junyang; Ye, Jinfeng; Kuang, Xiaoxuan; Liao, Wenjing; Song, Lijuan; Zhang, Xiaowen (Turkish Journal of Gastroenterology, 2023)
Background: Although observational studies have reported that depression is a risk factor for gastroesophageal reflux disease, it is difficult to determine the potential causal correlation. Thus, this study investigated the causal relevance of depression for gastroesophageal reflux disease using Mendelian randomization and provided new evidence for their association. Methods: Based on data from the UK Biobank, we assessed the causality of the 2 diseases by analyzing 135 458 severe depressive disorder cases and 41 024 gastroesophageal reflux disease cases. The causal inference was assessed using inverse-variance weighting, weighted median, Mendelian randomization–Egger, and weighted median methods. Simultaneously, pleiotropy and sensitivity analyses were used for quality control. Finally, we also explored whether depression affects gastroesophageal reflux disease through other risk factors. Results: A positive causal relationship between depression and gastroesophageal reflux disease was found in the inverse-variance weighted and weighted median methods, both of which were statistically significant [odds ratio = 1.011, 95% CI: 1.004-1.017, P =.001; odds ratio = 1.011, 95% CI: 1.004-1.020, P =.002)]. Sensitivity analyses were consistent with a causal interpretation, and the main deviation of genetic pleiotropy was not found (Intercept β = 0.0005; SE = 0.005, P =.908). The genetic susceptibility to depression was also associated with smoking, insomnia, and sleep apnea (odds ratio = 1.166, 95% CI: 1.033-1.316, P =.013; odds ratio = 1.089, 95% CI: 1.045-1.134; and odds ratio = 1.004, 95% CI: 1.001-1.006, P =.001, respectively). Conclusion: Our results verified a causal correlation that depression could slightly increase the risk of gastroesophageal reflux disease Cite this article as: Chen G, Xie J, Ye J, et al. Depression promotes gastroesophageal reflux disease: New evidence based on mendelian randomization. Turk J Gastroenterol. 2023;34(5):457-462.